Order-disorder degree of self-assembled clusters: Influence on photoluminescence emission and morphology of BaxSr1-xTiO3 nanocrystals - Souza, A. E. [UNESP]; Silva, R. A. [UNESP]; Santos, G. T. A. [UNESP]; Teixeira, S. R. [UNESP]; Antonio, S. G. [UNESP]; Moreira, M. L. [UNESP]; Volanti, D. P. [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2011)
BaxSr1-xTiO3 was prepared by the microwave-assisted hydrothermal method. The ceramic powder was characterized by X-ray diffraction, Raman, ultraviolet-visible and photoluminescence (PL) spectroscopies and scanning electron microscopy (FE-SEM). The results confirm that the powders consist of perovskite-type cubic and tetragonal crystalline structures. The Raman data show bands characterizing a multi-phonon process, suggesting the presence of defects, due to partial Sr/Ba substitution, resulting in different distorted clusters. A broad-band PL emission (blue light region) confirms the existence of these defects, which together with the results of ultraviolet-visible spectroscopy suggests non-uniformity in band structure. The distinct morphologies observed are associated with different clusters organization during the nucleation and growth of the BaxSr1-xTiO3 nanoparticles. (C) 2011 Elsevier B. V. All rights reserved.